Edukasi Dan Deteksi Dini Hipertrigliseridemia Dalam Rangka Pencegahan Dan Pengelolaan Gangguan kognitif Pada Kelompok Lanjut Usia - Anastasia Ratnawati Biromo; Fladys Jashina Mashadi; Yovian Timothy Satyo; Farell Christian; Edwin Destra (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
Cognitive impairment is a neuropsychological condition characterized by a decline in cognitive functions that interferes with daily activities. Cognitive impairment in elderly can lead to the decrease in quality of life. One of the factors causing cognitive impairment is high triglyceride level. Therefore, this community service activity is carried out to increase awareness and knowledge about hypertriglyceridemia and cognitive disorders through education and health screening. The activity method with PDCA is implemented to ensure a systematic and effective approach. Preventive efforts are needed through education on healthy eating pattern, physical activity, and routine screening to control triglyceride levels and prevent cognitive impairment in the elderly.